Ответ:
x = arctg(1/2) + kπ, або x = arctg(-2) + kπ
Объяснение:
2-3tgx=2tg²x
2tg²x + 3tgx - 2 = 0.
D = b² - 4ac, a = 2, b = 3, c = -2.
D = 3² - 4·2·(-2) = 25.
tgx = (-b ± √D) / 2a.
tgx₁ = (-3 + √25) / 4 = 1/2.
tgx₂ = (-3 - √25) / 4 = -2.
Відповідь: x = arctg(1/2) + kπ, або x = arctg(-2) + kπ, де k - ціле число.
Автор:
bebefhv9Ответ:
решение смотри на фотографии
Автор:
pandaahppДобавить свой ответ
Предмет:
Українська моваАвтор:
elisechapmanОтветов:
Смотреть
Предмет:
МатематикаАвтор:
camilla51Ответов:
Смотреть
Предмет:
Українська моваАвтор:
claudioОтветов:
Смотреть
Предмет:
Українська моваАвтор:
osborneОтветов:
Смотреть